Effects of Teacher-Delivered eCoaching on Paraeducators and Students with Autism Spectrum Disorder - Horn, A.L.; Rock, M.L.; Douglas, K.H.; Bean, K.M.; Layden, S.J.; Roitsch, J. (Education and Training in Autism and Developmental Disabilities, 2022)
Paraeducators often support students with the most intensive academic, life, and behavioral needs, which includes students with intellectual and other developmental disabilities (IDD; e.g., autism spectrum disorder; ASD), yet they typically enter the classroom with inadequate preparation to perform their roles effectively. Using a multiple-baseline research design replicated across participants, we evaluated the effects of job-embedded bug-in-ear (BIE) coaching delivered by the teacher on paraeducators’ use of behavior specific praise (BSP) while teaching transition-age students with ASD. Findings confirmed each of the three paraeducators immediately increased the percentage of occurrence and rate per minute in which they offered BSP. They sustained these high levels during fading. Further, the special education teacher, who served as the eCoach, and the paraeducators reported BIE was an effective form of paraeducator professional development. Finally, changes in expressive social and communicative behaviors were observed in student participants as a result of the intervention. These results extend literature on BSP and also help establish BIE coaching as an evidence-based practice for paraeducators. © Division on Autism and Developmental Disabilities.
Keywords: dept.cmd; peer-reviewed; ⛔ No DOI found

Making Sense of Word Reading Difficulties: Principles of Clinical Assessment - Zipoli, Richard P. (Communication Disorders Quarterly, 2022)
Speech-language pathologists (SLPs) are increasingly called upon to help assess students with word-recognition difficulties, including dyslexia. Although SLPs tend to have comparatively strong knowledge regarding the phonological awareness skills that support word reading, findings from survey research indicate that many SLPs report limited knowledge and training on word recognition and phonics. The purpose of this article is to provide a systematic framework for assessing and interpreting students’ word reading skills. Five potential components of word reading assessment will be examined: word recognition, phonological decoding, automaticity, performance with specific phonics patterns, and reading multimorphemic and multisyllabic words. Emphasis will be given to how specific test formats and procedures can be used to help identify patterns of word reading difficulty.
Keywords: assessment; automaticity; decoding; dept.cmd; peer-reviewed; phonics; reading; word recognition

Best Practice in Swallowing Assessment in COVID-19 - Warner, Heather; Young, Nwanmegha (Dysphagia, 2022)
The COVID-19 pandemic has significantly altered the world as we know it. Service delivery for the instrumental evaluation of dysphagia in hospitalized patients has been significantly impacted. In many institutions, instrumental assessment was halted or eliminated from the clinical workflow, leaving clinicians without evidence-based gold standards to definitively evaluate swallowing function. The aim of this study was to describe the outcomes of an early, but measured return to the use of instrumental dysphagia assessment in hospitalized patients during the COVID-19 pandemic. Data was extracted via a retrospective medical record review on all patients on whom a swallowing consult was placed. Information on patient demographics, type of swallowing evaluation, and patient COVID status was recorded and analyzed. Statistics on staff COVID status were also obtained. Over the study period, a total of 4482 FEES evaluations and 758 MBS evaluations were completed. During this time, no staff members tested COVID-positive due to workplace exposure. Results strongly support the fact that a measured return to instrumental assessment of swallowing is an appropriate and reasonable clinical shift during the COVID-19 pandemic.
Keywords: COVID; Deglutition; Dysphagia; FEES; Swallowing assessment; dept.cmd; peer-reviewed

Physical Activity, Sports Participation, and Psychosocial Health in Adolescents With Hearing Loss - DeLuca, Zara Waldman; Rupp, Kristie (Journal of Adolescent Health, 2022)
Purpose This study examined the association between hearing status (i.e., adolescents with and without hearing loss) and physical activity and sports participation. Secondarily, we explored the association between physical activity and sports participation and psychosocial outcomes among adolescents with hearing loss. Methods Analyses included 29,034 adolescents (52.1% male, 13.8 ± 2.3 (M ± SD) years) from the combined 2018–2019 National Survey of Children's Health. Adolescents were grouped by hearing status. Adjusted logistic regression models assessed physical activity level (i.e., 0, 1–3, 4–6, and 7 days/week) and sports participation (i.e., participation in sports within the past 12 months) by hearing status. Secondary analyses examined associations between physical activity and sports participation with psychosocial outcomes among adolescents with hearing loss adjusting for relevant confounders. Results Relative to their hearing peers, adolescents with hearing loss (n = 359) were 40% [adjusted odds ratio (AOR), 0.60; 95% confidence interval (CI), 0.44, 0.81], 43% [AOR, 0.57; 95% CI, 0.41, 0.80], and 33% [AOR, 0.67; 95% CI, 0.47, 0.95] less likely to engage in 1–3 days/week of physical activity, 4–6 days/week of physical activity, and meet physical activity guidelines, respectively. Further, adolescents with hearing loss were 31% [AOR, 0.69; 95% CI, 0.55, 0.85] less likely to participate in sports. Sports participation, but not physical activity, was associated with a significant reduction in the likelihood of experiencing adverse psychosocial outcomes among adolescents with hearing loss (p's < .05). Discussion Sports participation, but not physical activity, was associated with attenuated likelihood of experiencing adverse psychosocial outcomes in adolescents with hearing loss, suggesting unique characteristics of sports participation confer protection of psychosocial health. Increasing access to and reducing barriers to engagement in sports should be prioritized to improve psychosocial health in adolescents with hearing loss.
Keywords: Hearing loss; Physical activity; Psychosocial health; Sports participation; dept.cmd; dept.hms; peer-reviewed

Teaching Children with Autism to Create Multi-symbol Messages on Augmentative Alternative Communication Applications During Play - Gevarter, Cindy; Najar, Adriana Medina; Siciliano, Mariah (Advances in Neurodevelopmental Disorders, 2022)
Research involving the use of augmentative and alternative communication (AAC) applications on mobile technology devices for children with autism spectrum disorder (ASD) needs to expand beyond teaching simple requesting skills. Children’s abilities to create multi-symbol AAC messages is one skill that can be further explored.
Keywords: Augmentative alternative communication; Autism; Multi-symbol messages; Naturalistic intervention; dept.cmd; peer-reviewed